Longitudinal relationships between ideal body short-form video exposure, self-objectification, and preference for muscularity in a partner among Chinese young women - Lijun Zheng; Tiannan Zhao (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace)
Cultivation theory suggests that exposure to ideal body images may influence women’s self-objectification and partner preferences. According to selective exposure theory, women who self-objectify and prefer muscularity may choose media that aligns with their interests, particularly media showcasing idealized bodies. This longitudinal study examined the reciprocal relationships between ideal body short-form video exposure, self-objectification, and preference for muscularity in a partner in women. A total of 215 Chinese women (Mage = 21.1, SD = 2.5, range = 19–30) completed measures of ideal body short-form video exposure, self-objectification, and preference for partner muscularity at baseline and at 6-month follow-up. Cross-lagged panel analyses were used to analyze the reciprocal relationships between variables. The results revealed that viewing thin-ideal female body short-form video was associated with decreased self-objectification six months later. Viewing muscular-ideal male body short-form videos was not significantly associated with preference for muscularity after six months. However, preference for muscularity was associated with increased viewing of muscular-ideal male body short-form video six months later. Self-objectification was associated with an increased preference for muscularity in a partner six months later. The findings partially support the media selectivity theory.